Model Components Selection in Bayesian Model Averaging Using Occam's Window for Microarray Data - Ani Budi Astuti; Nur Iriawan; irhamah Irhamah; Heri Kuswanto (Journal of Natural A, 2014)
Microarray is an analysis for monitoring gene expression activity simultaneously. Microarray data are generated from microarray experiments having characteristics of very few number of samples where the shape of distribution is very complex and the number of measured variables is very large. Due to this specific characteristics, it requires special method to overcome this. Bayesian Model Averaging (BMA) is a Bayesian solution method that is capable to handle microarray data with a best single model constructed by combining all possible models in which the posterior distribution of all the best models will be averaged. There are several method that can be used to select the model components in Bayesian Model Averaging (BMA). One of the method that can be used is the Occam's Window method. The purpose of this study is to measure the performance of Occam's Window method in the selection of the best model components in the Bayesian Model Averaging (BMA). The data used in this study are some of the gene expression data as a result of microarray experiments used in the study of Sebastiani, Xie and Ramoni in 2006. The results showed that the Occam's Window method can reduce a number of models that may be formed as much as 65.7% so that the formation of a single model with Bayesian Model Averaging method (BMA) only involves the model of 34.3%. Keywords— Bayesian Model Averaging, Microarray Data, Model Components Selection, Occam's Window Method.